2018
DOI: 10.1111/bcpt.12989
|View full text |Cite
|
Sign up to set email alerts
|

Improving Medication Safety in Psychiatry – A Controlled Intervention Study of Nurse Involvement in Avoidance of Potentially Inappropriate Prescriptions

Abstract: The aim of this controlled, before-and-after study in the Department of Psychiatry in a university hospital in Denmark was to examine the potential effects and characteristics of nurses reviewing psychiatric patients' medication records to identify potentially inappropriate prescriptions (PIPs). The control group and the intervention group each consisted of two bed units chosen based on patients' diagnoses and age categories. There were 396 patients (age ≥18 years) included in the study. Senior clinical pharma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…There was a high incidence of PIP agent prescription in our study as can be comprehended from our results. Our findings are similar with a work conducted by Soerensen et al, 54 who reported that about 66% of their geriatric patients attending the psychiatry department of a university hospital were taking at least one PIP. In another retrospective, cross-sectional design study by Kolshus et al, 55 of the 65 patients (aged ⩾90 years), 23 (35.4%) received long-term benzodiazepines as PIP agents.…”
Section: Pip Agent Prescription In Geriatric Patientssupporting
confidence: 93%
“…There was a high incidence of PIP agent prescription in our study as can be comprehended from our results. Our findings are similar with a work conducted by Soerensen et al, 54 who reported that about 66% of their geriatric patients attending the psychiatry department of a university hospital were taking at least one PIP. In another retrospective, cross-sectional design study by Kolshus et al, 55 of the 65 patients (aged ⩾90 years), 23 (35.4%) received long-term benzodiazepines as PIP agents.…”
Section: Pip Agent Prescription In Geriatric Patientssupporting
confidence: 93%
“…The majority of studies (44 of 58) involved an individualized medication review 33,35–43,47–52,54–60,62,64–79,84,86–88 . Only few studies (16 of 48) reported active patient involvement in the review process 40–42,49,52,54–56,58–60,63,65,68,71,87 .…”
Section: Resultsmentioning
confidence: 99%
“…The percentage of female participants ranged between 7% and 78%. Only 2 studies reported somatic comorbidities 70,88 . Number of drugs before intervention ranged from 3 to 12.3 drugs per patient, with a median of 5.2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(Choo et al., 2010 ; Nursing & Midwifery Council, 2018 ) Nurses often appear to be the last barricade between patients and medication errors, because they are well‐positioned to identify drug‐related problems and minimize unnecessary drug‐related patient harm. (Dykes et al., 2010 ; Gabe et al., 2011 ; Henneman et al., 2010 ; Jordan et al., 2015 ; Rogers et al., 2008 ; Soerensen et al., 2018 ; Ulfvarson et al., 2007 ) In a previous study, 4,888 European nurses indicated monitoring therapeutic and adverse effects of medicines, monitoring medicines adherence, prescribing medicines and providing patient education and information about medicines are part of their clinical practice activities (De Baetselier, Van Rompaey, et al., 2020 ). A subsequent large‐scale interview study was able to confirm this active role in PC (De Baetselier, Dilles, et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%